Complementary Potentials of the Flour Blends Formulated From Sprouted Soybean (Glycine max), Sprouted Sorghum (Sorghum bicolor), and Unripe Plantain (Musa paradisiaca) Flour Intended for Infant Feeding - Okwunodulu, Innocent Nwazulu; Emmanuel, Inyang; Uluocha, Daniel Maduabuchi; Kalu, Okocha (Indonesian Association of Food Technologists, 2025)
High cost, as well as scarcity of commercial complementary foods, have long prevented the rural nursing mothers, especially those from developing countries, from readily accessing them. Consequently, the malnourished children become weaker and sicker, which calls for an option. Complementary formulation using readily available home-grown staples becomes the preferred option. In line with this, various locally formulated complementary foods have emerged from flour blends of cereals, legumes, and plantain, among others. Hence, this study is on the sprouted legume and cereal flour blends. The blends were investigated for proximate, vitamin, mineral, and functional properties with already established methods, while sensory properties were subjectively conducted on the hot water reconstituted blends using 25 semi-trained panelists. The results of proximate composition revealed that moisture, dry matter, protein, fiber, fat, ash, carbohydrate, and energy ranged respectively from 5.27-5.84%, 94.16-94.73%, 14.12-39.23%, 13.75-23.41%, 3.94-5.22%, 2.85-4.72%, 22.18-54.60% and 292.62-335.34 Kcal. Vitamins A, B1, B2, B3, and C, respectively, ranged from 682-930 µg/100g, 0.24-0.76 mg/100g, 0.16-0.27 mg/100g, 3.51-7.81 mg/100g, and 28.83-49.61 mg/100g. Calcium, magnesium, potassium, phosphorus, and iron, respectively, ranged from 18.08-32.12, 129.55-189.96, 450.53-796, 304.15-520.72, and 1.82-2.42 mg/100. Water absorption capacity, oil absorption capacity, bulk density, foam capacity, foam stability, wettability, gelatinization temperature and emulsion capacity respectively ranged from 1.53-2.30 g/g, 1.84-2.31 g/g, 0.69-0.74 g/ml, 24.42-31.15%, 38.81-72.50%, 49.92-82.12 sec, 61-68 ℃, and 58.15-70.17%. A sample blend of 40:30:30, respectively, for soybean, sorghum, and plantain flours was liked very much, while 30:40:30 were liked moderately. The complementary blends were nutrient-dense, highly acceptable, and therefore gold mine for complementary food production.